Academic women voicing narratives of gendered experiences - Ronksley-Pavia, Michelle; Neumann, Michelle M.; Manakil, Jane; Pickard-Smith, Kelly (Bloomsbury Academic, 2023)
"Through the lens of narratives, this book explores understandings of women's individual and collective experiences of working in academia, and reflects on women's experiences as always raced/classed, nuanced and complex. Each chapter provides a nuanced exploration of contemporary women's experiences in academia: whether from individual authors' research projects or a synthesis of projects; narrative framed literature reviews; metanalyses of current research; or counter-narratives of women's experiences in academia; of, from and by women working in academia. Bringing together these narratives, the editors develop collective understandings of how gender is shaped by these different structures, institutionalised systems and practices in academia, and how these (re)shape experiences and identity of women on an individual level in academia. They explore intersectionality and the variety of experiences relating to female academics: such as employment, promotion, authorship issues, research grant expectations and outcomes, imposter syndrome and gender parity. They explore how women attend to issues as they arise to bring together narrative collectives of problem solving, for women academics, from those at beginning of their careers to those well experienced."
Bevorzugte Informationsquelle Landing Page (Bloomsbury Collections), da kein Titelblatt vorhanden
Keywords: Women in higher education; Women scholars; Women college teachers; Educational leadership